Pengembangan Layanan Tes Berbasis Komputer dalam Pelatihan Kebahasaan - Wahyu Pramudita (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2021)
Computer- based test (CBT) becomes frequently applicable in the educational sectors. As the growing of objectiveness, facilitators need to consider this mode of assessment. Using much more adapted learning management system (Vettra Pro), CBT provides flexibility to map participants’ competency as well as tailored approachs, methods, and techniques. The purpose of the research is to design a computer based test for students’ academic assessment. The cycle of model, as part of research and development (R&D), used is needs analysis, design, development, and implementation. There are 15 participants of National Leadership Training-Threshold Level I, involved in this research. The researcher adapted interviews and observations as the data collection techniques. The results indicated that the product were valid and applicable for participants’ examination and the effectiveness of the learning system.